Current profile of cycling injuries: A retrospective analysis of a trauma centre level 1 in Queensland. (25th November 2015) - Neumann, Mirjam V; Eley, Rob; Vallmuur, Kirsten; Schuetz, Michael
Abstract: Objectives: One out of 50 injury‐related presentations to an ED is a transport‐related cycling injury. Detailed information about the most frequent mechanism of cycling injuries, sustained injuries and patterns are under‐reported. The objective of this research was to examine the pattern of injuries sustained by cyclists at a level 1 trauma centre. Methods: A retrospective review of data of injured cyclists admitted and treated at a level 1 trauma centre between 2011 and 2012 evaluated demographic data, mechanism of injury, injury pattern, economic costs and outcome. Results: Data of 261 patients (mean age of 39 years) were reviewed, of which 88% was male patients with an average age of 38 years. Non‐collision cycling injuries were reported in 55% of cases followed by collisions with other motor vehicles in 25.6% of cases. The mean injury severity score (ISS) was 9, but an ISS ≥ 12 was documented in 24%. Predominantly upper limb injuries (24.8%) were found, followed by injuries to the head and lower limb (each with 16.8%). Traumatic brain and chest injuries were equally seen in 8%. The overall length of stay was 4 days, and survival rate was 98%. Conclusion: This current data review reveals that non‐collision traffic crashes accounted for the majority of injuries in cyclists treated in this facility, and the upper limb has replaced the head as the most injured body part. With a growing number of cyclists, this information contributes to considerations to improve road safety and trauma management.